PERKEMBANGAN GREEN INTELLECTUAL CAPITAL DI INDONESIA: SCOPING REVIEW - Tandioga, Frenly Allen Samuel; Prihatin, Bayu Triyo (Accounting Department, Politeknik Negeri Bandung, 2023)
Environmental issues that have become a global priority have led to pressure from both regulations and public environmental awareness for companies to implement more environmentally friendly strategies. Scientific research has explained that the implementation of Green intellectual capital not only aims to reduce environmental impacts, but also provides a competitive advantage for organizations through cost reduction and improved company performance. The study aims to map the development of green intellectual capital in Indonesia through the results of previous studies with the scoping review method. The results of research in Indonesia show that green intellectual capital has a positive impact such as company performance, company sustainability, and competitive competition as well as several other topics. Through this research, companies can see the urgency of implementing green intellectual capital and can implement strategies that move towards sustainability and create a greater positive impact in the business environment and society as a whole.